Dynamic Progression of White Matter Hyperintensities in Alzheimer’s Disease and Normal Aging: Results from the Sunnybrook Dementia Study - Ramirez, Joel; McNeely, Alicia A.; Berezuk, Courtney; Gao, Fuqiang; Black, Sandra E. (Frontiers in Aging Neuroscience, 2016)
Although white matter hyperintensities (WMH), markers of cerebral small vessel disease (SVD), are believed to generally increase over time, some studies have shown sharp decreases after therapeutic intervention, suggesting that WMH progression may be more dynamic than previously thought. Our primary goal was to examine dynamic progression of WMH in a real-world sample of Alzheimer’s disease (AD) patients and normal elderly, with varying degrees of SVD. WMH volumes from serial MRI (mean=1.8 years) were measured from normal elderly (NC: n=44) and AD patients (n=113) with high and low SVD burden. Dynamic progression for each individual was measured using spatial overlap images to assess shrinkage, growth, and stable WMH volumes. Significant group differences were found for shrinkage (p<0.001), growth (p<0.001) and stable (p<0.001) WMH, where the AD high SVD group showed the largest changes relative to low SVD and NC. Our results suggest spatial progression measured at the individual patient level may be more sensitive to the dynamic nature of WMH.